2018
DOI: 10.1177/0269094218795595
|View full text |Cite
|
Sign up to set email alerts
|

Entering and leaving employment in deprived neighbourhoods undergoing area regeneration

Abstract: Concentrations of worklessness have been persistent in the UK for several decades but have not been tackled effectively by policy. An individualised approach to unemployment has existed, alongside employment policies without a strong geographical component. A reliance on area-based regeneration programmes has shifted from a property-led to a holistic approach, with the potential to address a range of factors associated with employment. To gauge the effectiveness and appropriateness of holistic area regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…We question whether this implies an assumption that young adults in prosperous areas have careers whereas those in deprived areas should become self-employed. Further research could open up such assumptions and examine enterprise alongside education, career prospects and other factors influencing young adults in deprived areas (Kearns and Mason, 2018;McGarvey, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We question whether this implies an assumption that young adults in prosperous areas have careers whereas those in deprived areas should become self-employed. Further research could open up such assumptions and examine enterprise alongside education, career prospects and other factors influencing young adults in deprived areas (Kearns and Mason, 2018;McGarvey, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Further research could open up such assumptions and examine enterprise alongside education, career prospects and other factors influencing young adults in deprived areas (Kearns and Mason, 2018;McGarvey, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of residents of the renovated estates, the causal processes may work (in non-mutually exclusive ways) through improvements in the physical quality of the occupied dwelling unit and/or social-interactive processes within the housing development (Kearns and Mason, 2018). Damp, mould, vermin, poor upkeep, overcrowding – conditions that often characterised social housing affected by the Stock Transfer – have been linked to adult stress, depression, hostility and inferior health outcomes (Chambers et al, 2015; Coley et al, 2013; Jacobs et al, 2009), all of which could impede an individual’s ability to find and keep a job.…”
Section: Potential Employment Impacts Of Social Housing Regeneration ...mentioning
confidence: 99%
“…Led primarily by local authorities and Community Planning Partnerships, the potential of place-based initiatives as a mechanism for addressing health inequities is coming increasingly to the fore within local policy and planning in Scotland (Improvement Service, 2016). Nevertheless, a large scale longitudinal study of the impacts of regeneration in Glasgow has shown that some strategies generally assumed to support people into employment, such as participation in training, had no effect; rather, support with physical and mental health and increasing physical activity were significant factors, while the participative aspects of regeneration were associated with psychosocial benefits, such as feelings of status and control, that are allied to positive mental wellbeing (Kearns and Mason, 2018). Participative approaches, supporting communities of place and of interest to successfully influence or manage change, can be seen as an entry point to increasing health equity for different people of working age, and beyond (see Clark and Wise, 2018).…”
Section: How Might We Drive Health Equity Forward?mentioning
confidence: 99%